NGTS clusters survey – I. Rotation in the young benchmark open cluster Blanco 1. Issue 1 (8th January 2020) - Gillen, Edward; Briegal, Joshua T; Hodgkin, Simon T; Foreman-Mackey, Daniel; Van Leeuwen, Floor; Jackman, James A G; McCormac, James; West, Richard G; Queloz, Didier; Bayliss, Daniel; Goad, Michael R; Watson, Christopher A; et al.
ABSTRACT: We determine rotation periods for 127 stars in the ∼115-Myr-old Blanco 1 open cluster using ∼200 d of photometric monitoring with the Next Generation Transit Survey. These stars span F5–M3 spectral types (1.2 M⊙ ≳ M ≳ 0.3 M⊙ ) and increase the number of known rotation periods in Blanco 1 by a factor of four. We determine rotation periods using three methods: Gaussian process (GP) regression, generalized autocorrelation function (G-ACF), and Lomb–Scargle (LS) periodogram, and find that the GP and G-ACF methods are more applicable to evolving spot modulation patterns. Between mid-F and mid-K spectral types, single stars follow a well-defined rotation sequence from ∼2 to 10 d, whereas stars in photometric multiple systems typically rotate faster. This may suggest that the presence of a moderate-to-high mass ratio companion inhibits angular momentum loss mechanisms during the early pre-main sequence, and this signature has not been erased at ∼100 Myr. The majority of mid-F to mid-K stars display evolving modulation patterns, whereas most M stars show stable modulation signals. This morphological change coincides with the shift from a well-defined rotation sequence (mid-F to mid-K stars) to a broad rotation period distribution (late-K and M stars). Finally, we compare our rotation results for Blanco 1 to the similarly aged Pleiades: the single-star populations in both clusters possess consistent rotation period distributions, which suggests that the angular momentum evolution of stars follows a well-defined pathway that is, at least for mid-F to mid-K stars, strongly imprinted by ∼100 Myr.